2005
DOI: 10.1002/jbm.a.30386
|View full text |Cite
|
Sign up to set email alerts
|

Collagen–carbon nanotube composite materials as scaffolds in tissue engineering

Abstract: Carbon nanotubes (CNT) are attractive for use in fiber-reinforced composite materials due to their very high aspect ratio, combined with outstanding mechanical and electrical properties. Composite materials comprising a collagen matrix with embedded CNT were prepared by mixing solubilized Type I collagen with solutions of carboxylated single-walled carbon nanotubes (SWNT) at concentrations of 0, 0.2, 0.4, 0.8, and 2.0 weight percent. Living smooth muscle cells were incorporated at the time of collagen gelation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
243
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(249 citation statements)
references
References 33 publications
6
243
0
Order By: Relevance
“…For instance, MacDonald et al [43], using aortic smooth muscle cells, showed that constructs containing 2 wt% CNTs in a 2 mg/mL collagen gel exhibited delayed gel compaction compared to that observed with lower concentrations of CNTs and to the control (absence of CNTs). Importantly, they also determined that the cell viability was consistently above 85% in all the constructs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, MacDonald et al [43], using aortic smooth muscle cells, showed that constructs containing 2 wt% CNTs in a 2 mg/mL collagen gel exhibited delayed gel compaction compared to that observed with lower concentrations of CNTs and to the control (absence of CNTs). Importantly, they also determined that the cell viability was consistently above 85% in all the constructs.…”
Section: Resultsmentioning
confidence: 99%
“…When collagen fibrillogenesis is initiated, CNTs may become incorporated into the triple-helical collagen molecule, or may remain as a separate phase linking the collagen fi bers. It is likely that the carboxyl and hydroxyl groups present on the surface of CNTs can form covalent and hydrogen bonds with amino groups extending from the collagen chains [41,43]. However, further theoretical and experimental work still needs to be performed to clarify these assumptions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isolated collagen monomers can re-assemble in vitro to form fibrils that resemble those in living tissue, with a characteristic 67 nm periodic structure called a D-period. [3,4] There is much interest in carbon nanotubes as a reinforcement additive for tissue engineering materials such as collagen gels, and cartilagenous simulants, [5][6][7][8][9]. In the present work, results are presented showing the in-vitro fibril formation of pepsin treated collagen in the presence of carbon nanotubes coated with polystyrene/polyanaline side chains, which resemble, somewhat, proteoglycan macromolecules, [10].…”
Section: Introductionmentioning
confidence: 83%
“…In vitro work has shown that several different cells types have been successfully grown on CNT/biopolymer composites. MacDonald found t h a t b l e n d s o f S W N T w i t h c o l l a g e n support smooth muscle cell growth (MacDonald, et al 2005). L929 mouse fibroblasts have been successfully grown on CNT scaffolds (Correa-Duarte, et al 2004) Abarrategi et al demonstrates the use of scaffolds composed of a major fraction of MWCNT (up to 89wt%) and a minor one of chitosan, and with a well-defined microchannel porous structure as biocompatible and biodegradable supports for culture growth.…”
Section: Biopolymer/cnt Composite As Tissue Scaffoldsmentioning
confidence: 99%